Combining ability and heterotic effects of maize (Zea mays) lines for drought tolerance using the line × tester method - ACHMAD AMZERI; SIGIT BUDI SANTOSO; FIRMANSYAH ADIPUTRA; SYAIFUL KHOIRI; KASWAN BADAMI; AHMAD SYAIFUL UMAM (Society for Indonesian Biodiversity, 2025)
Abstract. Amzeri A, Santoso SB, Adiputra F, Khoiri S, Badami K, Umam AS. 2025. Combining ability and heterotic effects of maize (Zea mays) lines for drought tolerance using the line × tester method. Biodiversitas 26: 748-760. Assembling superior varieties requires information on the combining ability and heterosis of several lines being tested to select lines that can be used as parents in assembling varieties. This research aimed to determine General Combining Ability (GCA), Specific Combining Ability (SCA), and heterosis of maize lines using the line x tester method on dry land. The genetic material used was 40 hybrids from crossing 20 lines with UTM08.5 and UTM09.6 testers. The research used a Randomized Complete Block Design (RCBD) with 62 genotypes (20 lines, 2 testers, 40 hybrids) as treatments and was repeated three times. The research results showed that lines that have a significant negative GCA value in harvest age character and can be used as parents in assembling early maturity maize varieties are T2S-5-11, DuS-5-24, Su-S-4-2-4, Su-S-4 -1-12, Su-S-4-1-12, and Su-S-4-1-15. Lines with a large positive GCA value and can be used as parents for assembling maize varieties with high production character are T2S-5-11, Su-S-4-2-4, Su-S-4-1-12, Su-S-4-1-15, and Su-S-4-3-16. The crosses T2S-5-11 × UTM08.5, Su-S-4-2-4 × UTM 08.5, and Su-S-4-1-15 × UTM08.5 had significant negative SCA values ??for harvest age and significant positive SCA values for the production per hectare character so that the three cross combinations can be used as candidates for the formation of early maturity and high production hybrid maize varieties. The best crosses are ES-5-24 × UTM09.6, T2S-5-11 × UTM08.5, T2S-5-11 × UTM09.6, and TS-5-20 × UTM09.6. They have positive heterosis for production per hectare character and negative heterosis for harvest age character.